2019
DOI: 10.1136/bcr-2019-230612
|View full text |Cite
|
Sign up to set email alerts
|

Adult intussusception associated with mesenteric Meckel’s diverticulum and antimesenteric ileal polyp

Abstract: Meckel’s diverticulum is the most common congenital abnormality affecting the gastrointestinal tract, affecting 4% of the general population. It is classically located on the antimesenteric border of the ileum within 100 cm of the ileocaecal valve. Complications may include haemorrhage, bowel obstruction, diverticulitis, perforation and malignancy. This report explores the case of intussusception in an adult, in association with a mesenteric Meckel’s diverticulum and adjacent benign polyp. A 40-year-old man pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Two patients were less than 6 months of age, ( 6 , 10 ) three between 1 and 6 years of age, ( 14 , 16 , 17 ) five between 15 and 30 years of age ( 5 , 7 , 13 , 18 , 19 ) and five between 40 and 50 years of age. ( 8 , 9 , 11 , 12 , 15 )…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two patients were less than 6 months of age, ( 6 , 10 ) three between 1 and 6 years of age, ( 14 , 16 , 17 ) five between 15 and 30 years of age ( 5 , 7 , 13 , 18 , 19 ) and five between 40 and 50 years of age. ( 8 , 9 , 11 , 12 , 15 )…”
Section: Discussionmentioning
confidence: 99%
“…From a geographical perspective, we observed that 15 publications came from five continents. One was from America (United States), (5) four from Europe (Italy, (6) France, (7) Spain (8) and the United Kingdom), (9) one from Africa (Tunisia), (10) seven from Asia (Japan, (11)(12)(13)(14) South Korea, (15) China (16) and Syria) (17) and two from Oceania (Australia). (18,19) Regarding the age of the patients included in this sample, there was a range from newborns to 49 years of age.…”
Section: Epidemiologymentioning
confidence: 99%
“…It was first described by John Fredrich Meckel in 1809, hence given the name Meckel's diverticulum. [3] The possible common complications associated with it include hemorrhage, obstruction, diverticulitis, hernia, and inflammation. [4] Rarely, Meckel's diverticulum can also cause intussusception.…”
Section: Introductionmentioning
confidence: 99%